Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/13548506.2016.1220600
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and coping in nasopharyngeal cancer: an explorative study in Western Europe

Abstract: Nasopharyngeal carcinoma (NPC) is the head and neck cancer with the greatest impact on patients' quality of life. The aim of this explorative study is to investigate the psychological distress, coping strategies and quality of life of NPC patients in the post-treatment observation period.Twenty-one patients disease-free for at least two years were assessed with a medical and a psycho-oncological evaluation. Clinically relevant depressive symptoms (CRD) were present in 23.8% of patients and 33.3% reported clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…These disorders occur about twice as often in females as males, and generally begin before the age of 25 [2]. Based on previous reports, the United States and Europe have a higher incidence rate than other countries [3,4]. Anxiety disorders are known to cause physical symptoms, including a rapid heart rate, shakiness and chest tightness, and even suicidal ideation, Research Dr. Hongzhuan Tan of a prebiotic trans-galactooligosaccharide in changing the colonic microflora and found that the prebiotic significantly improved anxiety scores (p<0.05) [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These disorders occur about twice as often in females as males, and generally begin before the age of 25 [2]. Based on previous reports, the United States and Europe have a higher incidence rate than other countries [3,4]. Anxiety disorders are known to cause physical symptoms, including a rapid heart rate, shakiness and chest tightness, and even suicidal ideation, Research Dr. Hongzhuan Tan of a prebiotic trans-galactooligosaccharide in changing the colonic microflora and found that the prebiotic significantly improved anxiety scores (p<0.05) [17].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, a metaanalysis focusing on the effect of probiotics on anxiety disorders is not available. Therefore, we conducted a systematic review of randomized controlled trials (RCTs) and meta-analyses to summarize evidence of the relationship between probiotics and anxiety, using RevMan software physical disability, and decreased quality of life [3]. Current treatment strategies include lifestyle changes, counselling, medications, or acupuncture [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…After three years, the intervention group had lower cognitive avoidance than the controls. Similarly, Ghiggia et al in study of 21 patients with a previous diagnosis of nasopharyngeal cancer enrolled at the First Ear Nose and Troat (1stENT) Division [17], Department of Surgical Sciences, at the University of Turin, during their post-treatment observation period. Results evidenced that fighting spirit; cognitive avoidance and fatalism were used more than hopelessness/ helplessness or anxious preoccupation.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of depression and anxiety have been observed in hospitalised NPC patients (Naing et al, ; Wen, Zhang, & Mingzhi, ), with gender, ethnicity, educational level and monthly income being implicated as influencing factors on anxiety and depression (Naing et al, ). Moreover, NPC patients with high anxiety or depressive symptoms may adopt dysfunctional coping strategies, such as hopelessness (Ghiggia et al, ; Hong et al, ). Mental status of NPC patients has been shown to be inversely related to quality of life, such that greater depression and anxiety associate with lower quality of life (Wu, Jiang, & Chen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, NPC patients with high anxiety or depressive symptoms may adopt dysfunctional coping strategies, such as hopelessness (Ghiggia et al, 2017;Hong et al, 2013). Mental status of NPC patients has been shown to be inversely related to quality of life, such that greater depression and anxiety associate with lower quality of life (Wu, Jiang, & Chen, 2015).…”
mentioning
confidence: 99%